CFRP U-Wraps and Spike Anchors for Enhancing the Flexural Performance of CFRP-Plated RC Beams - Abdalla, Jamal A. (2023)
Deterioration of infrastructure is a major challenge in the civil engineering industry. One of the methods that has been deemed effective in upgrading reinforced concrete (RC) structures is using externally bonded fiber-reinforced polymer (FRP) composites. However, the efficacy of this retrofitting technique is limited by the premature debonding failure of the FRP at the concrete-FRP interface; thus, the full capacity of the FRP is rarely utilized. Anchorage systems were proposed as a feasible solution to suppress or delay debonding failure. This paper presents an experimental investigation on the use of end U-wraps and carbon FRP (CFRP) spike anchors to anchor CFRP plates bonded to flexure-deficient RC beams. The experimental program consisted of seven RC beams with the length of the CFRP plate, type of anchorage, and the number of anchors as experimental variables. Test results indicated a remarkable enhancement in the ultimate load-carrying capacity when longer CFRP plates were used to strengthen the beams. In addition, anchoring the plates enhanced the strength of the CFRP-plated beams by 16–35% compared to the unanchored specimen, depending on the anchorage type and scheme. Finally, fib Bulletin 90 (2019) provisions provided the most accurate predictions of the moment capacity of the strengthened specimens.